Diagnostic and Prognostic Relevance of Serum Irisin Level in Patients with Pulmonary Embolism - Gurger, Mehtap; Telo, Selda; Yilmaz, Mustafa; Atescelik, Metin; Gul, Evrim; Goktekin, Mehmet C. (Clin Lab Publ, 2021)
Background: We aimed to determine the diagnostic and prognostic value of serum irisin level in patients with acute pulmonary embolism (PE) admitted to the emergency department. Methods: Ninety patients who underwent computed tomography pulmonary angiography (CTPA) due to suspected PE were included in the study. Demographic data, PE risk factors, and associated diseases, vital signs, Wells score, Revised Geneva score, pulmonary embolism severity index (PESI), and simplified PESI (sPESI) were recorded. Irisin levels were measured by enzyme linked-immunosorbent assay. Results: Serum irisin level in patients with confirmed PE (n = 45) was significantly lower than that in patients (n = 45) without PE (p = 0.001). On receiver operating characteristic curve analysis, use of optimal irisin cutoff level of 8.6 mu g/mL for diagnosis of PE was associated with 82.2% sensitivity, 60% specificity, 67.3% positive predictive value (PPV), and 77.1% negative predictive value (NPV) [area under the curve (AUC): 0.744, 95% confidence interval (CI): 0.641 - 0.830, p < 0.001)]. Use of optimal D-dimer cutoff level of 1,720 mu g/L was associated with 86.7% sensitivity, 62.2% specificity, 69.6% PPV, and 82.4% NPV (AUC: 0.801, 95% CI: 0.704 - 0.878, p < 0.001). Irisin level showed no significant correlation with Wells score or revised Geneva score; however, irisin level showed a significant negative correlation with PESI and sPESI. Conclusions: Patients with acute PE showed significantly lower serum levels of irisin. The sensitivity, specificity, NPV, and PPV of irisin level for diagnosis of PE were lower than those of D-dimer.
Keywords: irisin; pulmonary embolism